Religion and society in Middle Bronze Age Greece - Whittaker, Helène (Cambridge University Press, 2014)
The Middle Helladic period has received little attention, partially because of scholars' view of it as merely the prelude to the Mycenaean period and partially because of the dearth of archaeological evidence from the period. In this book, Helène Whittaker demonstrates that Middle Helladic Greece is far more interesting than its material culture might at first suggest. Whittaker comprehensively reviews and discusses the archaeological evidence for religion on the Greek mainland, focusing on the relationship between religious expression and ideology. The book argues that religious beliefs and rituals played a significant role in the social changes that were occurring at the time. The arguments and conclusions of this book will be relevant beyond the Greek Bronze Age and will contribute to the general archaeological debate on prehistoric religion.